The relationship between healthcare professionals’ mindful eating, eating attitudes, and body mass index - Arslan, Müge (Progress in Nutrition, 2019)
Purpose: This observational research study was conducted to determine the relationship between healthcare professionals’ eating attitudes, mindful eating, and body composition. Methods: Participants were 535 healthcare professionals, 325 (60%) working at Çorum (Turkey) Elitpark Hospital and 210 (40%) at Çorum Private Hospital. The participants filled a questionnaire with questions on demographic characteristics, body mass index (BMI), nutritional habits, Eating Attitudes Test, and Mindful Eating Scale. Results: The participants categorized as “other healthcare professionals” (28.6%) had the highest BMI value. The participants with impaired eating attitudes (92.2%) had high BMI values in general. The other healthcare professionals also constituted the occupational group with the highest impaired eating attitude score (66.9%). With regard to the magnitude of the relationship between mindful eating and BMI, obese and overweight people ranked first in terms of disinhibition, emotional eating, and interference. The lowest level of mindful eating was observed in the other healthcare professionals and auxiliary health personnel. Doctors were the occupational group with the highest level of mindful eating. The healthcare professionals with impaired eating attitudes had a statistically significantly higher average score on interference compared to those with normal eating attitude. Conclusion: The majority of the healthcare professionals participating in this study had high BMI values. Significant correlations were found among eating attitudes, mindful eating, and BMI. The other healthcare professionals and the auxiliary health personnel had the highest level of impaired eating attitudes and a low level of mindful eating. Level of Evidence: No level of evidence, basic science.